Subfissure-resistant soft photovoltaic module and preparation method thereof
By using unsaturated polyester resin pre-impregnated fiberglass cloth as the packaging material, the hidden cracking problem of gentle photovoltaic modules is solved, the components' anti-cracking ability and power generation performance are improved, and the service life is extended.
Patent Information
- Application Number
- CN202411767207.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-28
AI Technical Summary
Existing soft photovoltaic modules are prone to hidden cracking problems during use, resulting in power loss and reduced power generation performance, and thinning of materials leads to insufficient structural strength, making it difficult to effectively avoid hidden cracking.
Unsaturated polyester resin pre-preg glass fiber cloth is used as the direct packaging material for the battery cell, and a cryptoclase resistance film is formed through the lamination process to enhance the structural strength of the component and improve the cryptoclase resistance.
It effectively avoids hidden cracking problems in the production, transportation, installation and in extreme environments of gentle photovoltaic modules, and improves the power generation capacity and service life of the modules.
Smart Images

Figure CN119730402A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic modules, and in particular to a flexible photovoltaic module that is resistant to hidden cracks and a preparation method thereof. Background Art
[0002] Soft photovoltaic modules have attracted more and more attention due to their soft, thin and beautiful features. However, in the process of using soft photovoltaic modules, some quality problems have been constantly exposed, such as the problem of hidden cracks in photovoltaic modules, which refers to the phenomenon that tiny cracks appear in the internal cells of the photovoltaic modules after packaging. This phenomenon cannot be distinguished by the naked eye. Hidden cracks in photovoltaic modules will cause power loss of photovoltaic modules. Generally, cracks have little effect on the electrical performance of modules, while cracks have a very large impact on the power loss of modules. When photovoltaic modules are in use, the tiny cracks in the cells are gradually enlarged under the action of external forces, which in turn affects the power generation performance and service life of photovoltaic modules.
[0003] Common component cracks are divided into linear cracks and forked / net-shaped cracks. There are many reasons for the cracks in photovoltaic modules. The production, packaging, transportation, installation and environmental stress after installation of photovoltaic modules: wind, snow, hail and temperature changes may cause cracks, but in the final analysis, the strength of photovoltaic modules still needs to be improved. However, most manufacturers of existing materials for solar photovoltaic modules have adopted the means of reducing the thickness or amount of raw materials. This development trend further reduces the structural strength of the module. The thinning of materials and the improvement of the strength of the module itself are contradictory. In addition, improper subsequent installation or excessive pressure often causes cracks, which affects the photoelectric conversion efficiency. Therefore, it is imperative to develop new soft photovoltaic modules that are resistant to cracks! Summary of the invention
[0004] Purpose of the invention: In view of the problems and shortcomings in the prior art, the present invention provides a crack-resistant and flexible photovoltaic component and a manufacturing method which has a simple structure and is of great help in solving the problems in the prior art.
[0005] The specific technical solutions are as follows:
[0006] A method for preparing a crack-resistant and flexible photovoltaic module, the method comprising the following steps:
[0007] S1, preparing an anti-hidden crack film, and dividing the anti-hidden crack film into two parts, one part is a first anti-hidden crack film, and the other part is a second anti-hidden crack film;
[0008] S2, laying a back sheet, a high-cutoff encapsulation film and a first anti-hidden crack film in sequence from bottom to top on the operating table according to a stacking structure, and placing a battery layer on the laid first anti-hidden crack film to complete the bus connection, wherein the battery layer includes a plurality of solar cell strings;
[0009] S3. Lay the second anti-hidden crack film, high-transmittance packaging film, and transparent packaging front layer on the battery layer from bottom to top in sequence, and laminate the back panel, high-cutoff packaging film, first anti-hidden crack film, battery layer, second anti-hidden crack film, high-transmittance packaging film, and transparent packaging front layer into an anti-hidden crack and flexible photovoltaic module through a laminator.
[0010] Furthermore, the S1 preparation of the anti-crack film comprises the following steps:
[0011] S11, adding a curing agent to the unsaturated polyester resin solution, stirring evenly at 70-80° C. to obtain a mixed solution A;
[0012] S12, adding a promoter to the mixed solution A, stirring evenly at 70-80° C. to obtain a mixed solution B;
[0013] S13, applying glue to the mixed solution B and pre-impregnating it with glass fiber cloth to obtain an anti-hidden crack film.
[0014] Furthermore, the unsaturated polyester resin is any one or more of the following: phthalic acid type, isophthalic acid type, neopentyl glycol type, bisphenol A type, vinyl ester type, halogenated unsaturated polyester resin, and the linear thermal expansion coefficient of the unsaturated polyester resin is 132×10 -6 ~140×10 -6 / ℃, the mass of unsaturated polyester resin is equivalent to 25% to 45% of the mass of prepreg.
[0015] Further, the curing agent is any one of the following: dicyandiamide 100S, EQ14, DDA-5, tert-butyl perbenzoate, tert-butyl peroxy-2-ethylhexanoate, cyclohexanone peroxide;
[0016] The accelerator is any one of the following: diurea EQ20, UR300, UR500;
[0017] The thickness of the finished product is 0.1-0.25 mm.
[0018] Furthermore, the prepreg process in step S13 includes the following steps:
[0019] Firstly, the mixed liquid B is placed in a glue coating machine, and the thickness or surface density of the glue film is detected by an infrared instrument. The temperature of the glue film is lowered to room temperature by a cooling plate to reduce its curing degree, so as to obtain a glue film used for prepreg. Then, the glue film is drawn out from the upper and lower glue film rollers of the prepreg machine through a prepreg process, and forms a sandwich structure with the glass fiber cloth, and passes through hot pressing rollers in turn to melt the resin matrix, and the glass fiber cloth is embedded in the resin matrix. The temperature of the prepreg is cooled to reduce to room temperature, and finally trimming, laminating and winding are performed to obtain an unsaturated polyester resin glass fiber cloth prepreg, i.e., an anti-hidden crack film.
[0020] Furthermore, the high cutoff packaging film and high transmittance packaging film are made of EVA, POE, or EPE.
[0021] Furthermore, the backboard includes any one of the following: CPC backboard, KPF backboard, glass fiber reinforced polypropylene backboard, epoxy glass fiber prepreg, acrylic powder coated glass fiber backboard.
[0022] Furthermore, the transparent encapsulation front layer includes any one of the following: acrylic powder coated glass fiber transparent encapsulation front layer, transparent FFC transparent encapsulation front layer, epoxy glass fiber prepreg, ETFE film, PVDF film.
[0023] Furthermore, the colors of the epoxy glass fiber prepreg include: transparent, white, and black.
[0024] Furthermore, during the lamination process, the vacuuming time is 380 to 420 seconds, the pressure holding time is 1420 to 1720 seconds, the lamination temperature is 140 to 160° C., and the lamination time is 25 to 40 minutes.
[0025] On the other hand, the present invention also provides a light and flexible photovoltaic component that is resistant to hidden cracks, which is prepared by the above-mentioned method for preparing the light and flexible photovoltaic component that is resistant to hidden cracks.
[0026] Beneficial effect: The present invention uses unsaturated polyester resin pre-impregnated glass fiber cloth as the direct packaging material for the battery cell. Compared with the traditional use of EVA or POE film as the direct packaging material for the battery cell, its strength is higher after the lamination is fully cured, which can better protect the battery cell and improve the ability of the flexible photovoltaic module to resist hidden cracks. It can effectively avoid the problem of hidden cracks in the production, transportation, installation process of the flexible photovoltaic module and in extreme environments such as hail and strong winds, thereby improving the power generation capacity of the photovoltaic module and extending the service life of the photovoltaic module! BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the structure of an embodiment of a light and flexible photovoltaic component that resists hidden cracks in the present application;
[0028] Wherein: 101, transparent packaging front layer; 102, high-transparency packaging film; 103, second anti-hidden crack film, 104 battery cell layer; 105, first anti-hidden crack film, 106, high-cutoff packaging film; 107, backplane. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0030] Example
[0031] A method for preparing a crack-resistant and flexible photovoltaic module, the method comprising the following steps:
[0032] S1, preparing an anti-hidden crack film, and dividing the anti-hidden crack film into two parts, one part is a first anti-hidden crack film, and the other part is a second anti-hidden crack film;
[0033] S2, laying a back sheet, a high-cutoff encapsulation film and a first anti-hidden crack film in sequence from bottom to top on the operating table according to a stacking structure, and placing a battery layer on the laid first anti-hidden crack film to complete the bus connection, wherein the battery layer includes a plurality of solar cell strings;
[0034] S3. Lay the second anti-hidden crack film, high-transmittance packaging film, and transparent packaging front layer on the battery layer from bottom to top in sequence, and laminate the back panel, high-cutoff packaging film, first anti-hidden crack film, battery layer, second anti-hidden crack film, high-transmittance packaging film, and transparent packaging front layer into an anti-hidden crack and flexible photovoltaic module through a laminator.
[0035] Furthermore, the S1 preparation of the anti-crack film comprises the following steps:
[0036] S11, adding a curing agent to the unsaturated polyester resin solution, stirring evenly at 70-80° C. to obtain a mixed solution A;
[0037] S12, adding a promoter to the mixed solution A, stirring evenly at 70-80° C. to obtain a mixed solution B;
[0038] S13, applying glue to the mixed solution B and pre-impregnating it with glass fiber cloth to obtain a finished product.
[0039] Furthermore, the unsaturated polyester resin is any one or more of the following: phthalic acid type, isophthalic acid type, neopentyl glycol type, bisphenol A type, vinyl ester type, halogenated unsaturated polyester resin, and the linear thermal expansion coefficient of the unsaturated polyester resin is 132×10 -6 ~140×10 -6 / ℃, the mass of unsaturated polyester resin is equivalent to 25% to 45% of the mass of prepreg.
[0040] Further, the curing agent is any one of the following: dicyandiamide 100S, EQ14, DDA-5, tert-butyl perbenzoate, tert-butyl peroxy-2-ethylhexanoate, cyclohexanone peroxide;
[0041] The accelerator is any one of the following: diurea EQ20, UR300, UR500;
[0042] The thickness of the finished product is 0.1-0.25 mm.
[0043] Furthermore, the prepreg process in step S13 includes the following steps:
[0044] Firstly, the mixed liquid B is placed in a glue coating machine, and the thickness or surface density of the glue film is detected by an infrared instrument. The temperature of the glue film is lowered to room temperature by a cooling plate to reduce its curing degree, so as to obtain a glue film used for prepreg. Then, the glue film is drawn out from the upper and lower glue film rollers of the prepreg machine through a prepreg process, and forms a sandwich structure with the glass fiber cloth, and passes through hot pressing rollers in turn to melt the resin matrix, and the glass fiber cloth is embedded in the resin matrix. The temperature of the prepreg is cooled to reduce to room temperature, and finally trimming, laminating and winding are performed to obtain an unsaturated polyester resin glass fiber cloth prepreg, i.e., an anti-hidden crack film.
[0045] Furthermore, the high cutoff packaging film and high transmittance packaging film materials include: EVA, POE, and EPE.
[0046] The EPE is a three-layer structure of EVA / PET / EVA.
[0047] Furthermore, the backboard includes any one of the following: CPC backboard, KPF backboard, glass fiber reinforced polypropylene backboard, epoxy glass fiber prepreg, acrylic powder coated glass fiber backboard.
[0048] Furthermore, the transparent encapsulation front layer includes any one of the following: acrylic powder coated glass fiber transparent encapsulation front layer, transparent FFC transparent encapsulation front layer, epoxy glass fiber prepreg, ETFE film, PVDF film.
[0049] Furthermore, the colors of the epoxy glass fiber prepreg include: transparent, white, and black.
[0050] Furthermore, during the lamination process, the vacuuming time is 380 to 420 seconds, the pressure holding time is 1420 to 1720 seconds, the lamination temperature is 140 to 160° C., and the lamination time is 25 to 40 minutes.
[0051] On the other hand, the present invention also provides a light and flexible photovoltaic component that is resistant to hidden cracks, which is prepared by the above-mentioned method for preparing the light and flexible photovoltaic component that is resistant to hidden cracks.
[0052] Beneficial effect: The present invention uses unsaturated polyester resin pre-impregnated glass fiber cloth as the direct packaging material for the battery cell. Compared with the traditional use of EVA or POE film as the direct packaging material for the battery cell, its strength is higher after the lamination is fully cured, which can better protect the battery cell and improve the ability of the flexible photovoltaic module to resist hidden cracks. It can effectively avoid the problem of hidden cracks in the production, transportation, installation process of the flexible photovoltaic module and in extreme environments such as hail and strong winds, thereby improving the power generation capacity of the photovoltaic module and extending the service life of the photovoltaic module!
[0053] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a crack-resistant and flexible photovoltaic module, characterized in that: The method comprises the following steps: S1, preparing an anti-hidden crack film, and dividing the anti-hidden crack film into two parts, one part is a first anti-hidden crack film, and the other part is a second anti-hidden crack film; S2, laying a back sheet, a high-cutoff encapsulation film and a first anti-hidden crack film in sequence from bottom to top on the operating table according to a stacking structure, and placing a battery layer on the laid first anti-hidden crack film to complete the bus connection, wherein the battery layer includes a plurality of solar cell strings; S3. Lay the second anti-hidden crack film, high-transmittance packaging film, and transparent packaging front layer on the battery layer from bottom to top in sequence, and laminate the back panel, high-cutoff packaging film, first anti-hidden crack film, battery layer, second anti-hidden crack film, high-transmittance packaging film, and transparent packaging front layer into an anti-hidden crack and flexible photovoltaic module through a laminator.
2. The method for preparing a crack-resistant and flexible photovoltaic module according to claim 1, characterized in that: The step S1 of preparing the anti-crack film comprises the following steps: S11, adding a curing agent to the unsaturated polyester resin solution, stirring evenly at 70-80° C. to obtain a mixed solution A; S12, adding a promoter to the mixed solution A, stirring evenly at 70-80° C. to obtain a mixed solution B; S13, applying glue to the mixed solution B and pre-impregnating it with glass fiber cloth to obtain an anti-hidden crack film.
3. The method for preparing a crack-resistant and flexible photovoltaic module according to claim 2, characterized in that: The unsaturated polyester resin is any one or more of the following: phthalic acid type, isophthalic acid type, neopentyl glycol type, bisphenol A type, vinyl ester type, halogenated unsaturated polyester resin, and the linear thermal expansion coefficient of the unsaturated polyester resin is 132×10 -6 ~140×10 -6 / ℃, the mass of unsaturated polyester resin is 25% to 45% of the mass of prepreg.
4. The method for preparing a crack-resistant and flexible photovoltaic module according to claim 2, characterized in that: The curing agent is any one of the following: dicyandiamide 100S, EQ14, DDA-5, tert-butyl perbenzoate, tert-butyl peroxy-2-ethylhexanoate, cyclohexanone peroxide; The accelerator is any one of the following: diurea EQ20, UR300, UR500; The thickness of the anti-crack film is 0.1-0.25 mm.
5. The method for preparing a crack-resistant and flexible photovoltaic module according to claim 2, characterized in that: The prepreg process in step S13 includes the following steps: Firstly, the mixed liquid B is placed in a glue coating machine, and the thickness or surface density of the glue film is detected by an infrared instrument. The temperature of the glue film is lowered to room temperature by a cooling plate to reduce its curing degree, so as to obtain a glue film used for prepreg. Then, the glue film is drawn out from the upper and lower glue film rollers of the prepreg machine through a prepreg process, and forms a sandwich structure with the glass fiber cloth, and passes through hot pressing rollers in turn to melt the resin matrix, and the glass fiber cloth is embedded in the resin matrix. The temperature of the prepreg is cooled to reduce to room temperature, and finally trimming, laminating and winding are carried out to obtain an anti-hidden crack film.
6. The method for preparing a crack-resistant and flexible photovoltaic module according to claim 1, characterized in that: The high cutoff packaging film and high transmittance packaging film materials include: EVA, POE, and EPE.
7. The method for preparing the anti-hidden crack flexible photovoltaic module according to claim 1, characterized in that: The backboard includes any one of the following: CPC backboard, KPF backboard, glass fiber reinforced polypropylene backboard, epoxy glass fiber prepreg, acrylic powder coated glass fiber backboard.
8. The method for preparing a crack-resistant and flexible photovoltaic module according to claim 1, characterized in that: The transparent encapsulation front layer includes any one of the following: acrylic powder coated glass fiber transparent encapsulation front layer, transparent FFC transparent encapsulation front layer, epoxy glass fiber prepreg, ETFE film, PVDF film.
9. The method for preparing a crack-resistant and flexible photovoltaic module according to claim 1, characterized in that: During the lamination process, the vacuuming time is 380 to 420 seconds, the pressure holding time is 1420 to 1720 seconds, the lamination temperature is 140 to 160° C., and the lamination time is 25 to 40 minutes.
10. A light and flexible photovoltaic module with anti-hidden cracking, characterized in that: The anti-hidden crack and flexible photovoltaic component is prepared by the method for preparing the anti-hidden crack and flexible photovoltaic component according to any one of claims 1 to 9.
Citation Information
Cited By
Flexible solar panel and preparation method thereof
CN120379353A
A flexible solar panel and a method of manufacturing the same
CN120379353B
Crystal laminated prefabricated member, curved-surface photovoltaic module and packaging process of curved-surface photovoltaic module
CN120957498A